Ballistic Fractures During The 2003 Gulf Conflict – Early Prognosis And High Complication Rate - Hinsley, D E; Phillips, SL; Clasper, J C (BMJ military health, 2006)
Background Ballistic fractures are devastating injuries often necessitating extensive reconstructive surgery or amputation, particularly if associated with high-energy transfer wounds. Infective complications are common, particularly in the austere environment encountered in war. We present the management and early outcome of these injuries with reference to the mechanism of injury and bony injury. Method Data on ballistic fractures was collected prospectively during the ‘warfighting’ phase of the 2003 Gulf Conflict, between 19th March and 20th May. Fractures were scored using the Red Cross Fracture classification and early outcome analysed. Results Thirty-nine patients, with 50 ballistic fractures, were treated by British military surgeons. Patients were predominantly Iraqi (90%) and 50 per cent of ballistic fractures were caused by bullets. Seventeen upper limb fractures and 33 lower limb fractures were sustained. There were seven traumatic amputations, and a further 2 limbs were amputated primarily. Methods of primary stabilisation for the remaining 41 fractures were: external fixation (22%), POP (14.5%), K-wires (14.5%) traction (10%), and no stabilisation (39%). Seven individuals were evacuated early after primary surgery, hence 43 ballistic fractures were available for follow-up. 13/43 (30%) of wounds became infected, 5/43 (11.5%) were deep infections necessitating surgical drainage. There were 4 late amputations (9.5%), 3 of which had initially been managed by external fixation. Infection occurred significantly more often in gunshot fractures (10/21, 48%), wounds closed primarily – against the principles of war surgery (4/5, 80%) and intra-articular fractures (3/3, 100%) (p=0.022, 0.024 and 0.023 respectively). Differing methods of stabilisation had no bearing on the rate of postoperative infection. Conclusion Ballistic fractures remain a challenge for trauma surgeons in times of war and still have a poor prognosis. Further work is required to determine the optimal treatment of these injuries during conflicts. In addition, there still seems to be a continued need to re-learn the principles of war surgery in order to minimise complications and optimise functional recovery.